The Expression of Adipophilin Is Frequently Found in Solid Subtype Adenocarcinoma and Is Associated with Adverse Outcomes in Lung Adenocarcinoma - Sun Ah Shin; Hee Young Na; Ji Young Choe; Doohyun Chung; Mira Park; Sohee Oh; Ji Eun Kim (Journal of Pathology and Translational Medicine, 2018)
Background The up-regulation of the lipogenic pathway has been reported in many types of malignant tumors. However, its pathogenic role or clinical significance is not fully understood. The objective of this study was to examine the expression levels of adipophilin and related hypoxic signaling proteins and to determine their prognostic impacts and associations with the pathologic characteristics of lung adenocarcinoma. Methods Expression levels of adipophilin, heat shock protein 27 (HSP27), carbonic anhydrase IX, and hypoxia-inducible factor 1α were examined by immunohistochemical staining using tissue microarray blocks. Correlations between protein expression levels and various clinicopathologic features were analyzed. Results A total of 230 cases of primary adenocarcinoma of the lung were enrolled in this study. Adipophilin expression was more frequent in males and with the solid histologic type. It was correlated with HSP27 expression. Patients with adipophilin-positive adenocarcinoma showed a shorter progression-free survival (PFS) (median PFS, 17.2 months vs 18.4 months) in a univariable survival analysis, whereas HSP27 positivity correlated with favorable overall survival (OS) and PFS. In a multivariable analysis, adipophilin and HSP27 were independent prognostic markers of both OS and PFS. Conclusions Activated lipid metabolism and the hypoxic signaling pathway might play a major role in the progression of lung adenocarcinoma, especially in the solid histologic type.